Beaver dams and associated pre/during/post-fire Normalized Difference Vegetation Index (NDVI) in Western U.S.A. - Emily Fairfax; Andrew Whittle (PANGAEA, 2020)
These data are from 5 wildfires that burned in recent decades in the western United States. The data is NDVI along creeks within the wildfire perimeters in areas that do and do not have beaver damming, as well as path files for dam locations. Data description is in metadata file. For more information please contact Emily Fairfax via website contact form (emilyfairfaxscience.com).